PENGARUH BUDAYA “SATU TUNGKU TIGA BATU” TERHADAP TOLERANSI BERAGAMA MASYARAKAT WERBA FAKFAK PAPUA - Delvia Pandaiya; Marthinus Ngabalin; Lindra Yolanda Camerling (SEKOLAH TINGGI TEOLOGI KIBAID, 2021)
People in Werba village, Fakfak Regency, and Papua live in a plurality of religions with a high religious tolerance. Within a family, there can be three different religions: Protestant Christianity, Islam and Catholicism. Interfaith marriage is accepted and practised as a matter, of course. In the construction of a house of worship, there are committee members from other religions. This lifestyle seems to be influenced by the local culture. This study aims to describe the influence of culture in a pluralist lifestyle with high religious tolerance. The method used is descriptive-qualitative. The data collection technique was interviews with informants from traditional and religious leaders in Werba village, Fakfak District, Papua. The results showed that the basic pluralist life and religious tolerance in Werba village were influenced by the local community's powerful kinship system. The main philosophy is one stove of three stones which means one family of three religions. Kinship, kinship, brotherhood is the primary basis of social life, including religious life.